Acupuncture and responses of immunologic and endocrine markers during competition - Akimoto, T.; Nakahori, C.; Aizawa, K.; Kimura, F.; Fukubayashi, T.; Kono, I. (Medicine & Science in Sports & Exercise, 2003)
INTRODUCTION: Acupuncture is used to modulate the physical well-being of athletes in Asian countries. However, there is little information on the immediate effects of acupuncture treatment on physiological or psychological responses to exercise. PURPOSE: The purpose of this study was to examine the effect of acupuncture treatment on the physical well-being of elite female soccer players during a competition period. METHODS: Subjects were divided into two groups: those who received acupuncture treatment (18.1 +/- 2.3 yr [+/-SD], N = 9) and a control group (17.7 +/- 2.8 yr, N = 12). In the treatment group, acupuncture stimulus was applied at LI 4 (Goukoku), ST 36 (Ashi-sanri) for 20 min, and ST 6 (Kyosya), LU 6 (Ko-sai) points for 15 min 4 h after the game every night during the competition period. The measured parameters included salivary secretory immunoglobulin A (SIgA) level, cortisol level in saliva, subjective rating of physical well-being, and profile of mood states (POMS). RESULTS: The following were the main results: 1). Exercise-induced decrease of salivary SIgA and increase of salivary cortisol were inhibited by acupuncture. 2). Acupuncture improved subjective rating of muscle tension and fatigue. 3). The POMS score was modulated by acupuncture. CONCLUSION: These results support the effectiveness of acupuncture for physical and mental well-being of athletes.